Influence Of Post Harvest Calcium Chloride Treatment And Shrink Film Packaging On Storage Life Of Pear Fruits (Applied Biological Research, 2016)
To enhance the storage life of pear cv. ‘Punjab Beauty’, fruits were  dipped in aqueous solution of calcium chloride (1.5 and 2.5%) for 5  min., packed in corrugated fibre board (CFB) boxes or shrinkfilm trays  and stored at 0-1oC with 90-95% RH for 67 days. Untreated fruits were  dipped in fresh water only and kept in CFB boxes. The weight loss was  appreciably reduced in CaCl2 treated + shrink wrapped fruits. CaCl2  treatment @ 1.5% and shrink film tray packaging proved effective in  maintaining the firmness and acid content of fruits. Maximum sensory  quality of fruits was recorded after 45 days in fruits treated with CaCl2  @ 2.5% + CFB packing. Soluble solids content in fruit juice was highest  after 60 day of storage in all the treatments. Combination of shrink film tray packaging + CaCl2 @ 1.5% treatment was effective in minimizing  the physiological loss in weight of fruits and maintaining the fruit  quality for 60 days under storage.
Keywords: Calcium chloride; fruit quality; pear; shrink film tray packaging; storage